1995
DOI: 10.1073/pnas.92.26.12505
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of cytochrome P450 in oxime production in glucosinolate biosynthesis as demonstrated by an in vitro microsomal enzyme system isolated from jasmonic acid-induced seedlings of Sinapis alba L.

Abstract: An in vitro enzyme system for the conversion of amino acid to oxime in the biosynthesis of glucosinolates has been established by the combined use of an improved isolation medium and jasmonic acid-induced etiolated seedlings of Sinapis alba L. An 8-fold induction of de novo biosynthesis of the L-tyrosine-derived p-hydroxybenzylglucosinolate was obtained in etiolated S. alba seedlings upon treatment with jasmonic acid. Formation of inhibitory glucosinolate degradation products upon tissue homogenization was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 21 publications
0
51
0
Order By: Relevance
“…12). In microsomal enzyme systems isolated from S. alba, T. majus, and C. papaya, tyrosine or phenylalanine are converted to the corresponding aldoximes by cytochrome P450-dependent monooxygenases, as evidenced by photoreversible carbon monoxide inhibition and other inhibitor studies (13)(14)(15)(16). Biochemical studies with microsomal preparations from Brassica napus L. have indicated that the conversion of homophenylalanine, dihomo-, trihomo-, and tetrahomomethionine to the corresponding aldoximes is not affected by carbon monoxide and 2 P. Brown and J. Gershenzon, personal communication.…”
Section: Fig 2 N-terminal Amino Acid Sequences Deduced From the Cypmentioning
confidence: 99%
See 1 more Smart Citation
“…12). In microsomal enzyme systems isolated from S. alba, T. majus, and C. papaya, tyrosine or phenylalanine are converted to the corresponding aldoximes by cytochrome P450-dependent monooxygenases, as evidenced by photoreversible carbon monoxide inhibition and other inhibitor studies (13)(14)(15)(16). Biochemical studies with microsomal preparations from Brassica napus L. have indicated that the conversion of homophenylalanine, dihomo-, trihomo-, and tetrahomomethionine to the corresponding aldoximes is not affected by carbon monoxide and 2 P. Brown and J. Gershenzon, personal communication.…”
Section: Fig 2 N-terminal Amino Acid Sequences Deduced From the Cypmentioning
confidence: 99%
“…Independent biochemical studies have indicated that three different enzyme systems are involved in this step, namely cytochrome P450-dependent monooxygenases, flavincontaining monooxygenases, and peroxidases (12). The aromatic amino acids (tyrosine and phenylalanine) are converted to the corresponding aldoximes by cytochrome P450-dependent monooxygenases in microsomes isolated from Sinapis alba L., Tropaeolum majus L., and Carica papaya L. (13)(14)(15)(16). Conversion of homophenylalanine and chain elongated methionine homologues into the corresponding aldoximes by microsomal preparations of Brassica spp.…”
mentioning
confidence: 99%
“…Because genes involved in Trp biosynthesis and its secondary metabolites are induced in response to pathogens (22,31,32), we tested whether CYP79B2 mRNA expression is induced in response to bacterial infection. A Northern blot was prepared from Col-0 Arabidopsis leaves that were infected for various times with either the virulent strain P. syringae pv.…”
Section: Cyp79b2 Overexpression In Plants Confers Resistance To Toxicmentioning
confidence: 99%
“…In Arabidopsis, glucosinolates are biosynthesized from a variety of typical protein amino acids (methionine, tryptophan, and phenylalanine) and their chain-elongated analogs. The first step in glucosinolate biosynthesis is the oxidation of the amino group to an oxime moiety by amino acid-specific cytochrome P450 monooxygenases (Du et al, 1995;Wittstock and Halkier, 2000). After a thiohydroximate intermediate is formed, sequential transfer of glucose and sulfate residues creates the basic glucosinolate skeleton (Halkier and Du, 1997).…”
Section: Introductionmentioning
confidence: 99%